(untitled) (Scientific journal of the Fergana State University, 2024)
Sociocultural technologies are understood as all forms and actions that help to distinguish, understand and comprehend the values of culture and art. In a country with an underdeveloped culture, there will be no social development, since they are interconnected. The activity of sociocultural technologies is manifested in theoretical and practical activities and forms the basis of aesthetic methodology. To do this, it is necessary to make the design of the system of sociocultural technologies interesting and complex in accordance with the times, as well as to develop a technology for the development processes in education, culture and art. This article discusses the methodology for using sociocultural technologies to improve the aesthetic thinking of young people.